Theory of Empowerment in Female Cyber Victimization - Siriporn Santre (International Journal of Indian Psychȯlogy, 2022)
The pervasiveness of digital technology in people’s lives is widely acknowledged, and it is potential for risky behaviors to be occurred in online. Females have been observed to face more cyber victimization than males due to the gender issue. Despite the rise in cyber victimization, research into the theoretical backgrounds of such online behaviors has been limited, but using the theory of empowerment, the female victim would more accurately pave a path that could lead to a reduction in the problem. This study provides a brief overview of the meaning and significance of empowerment theory, concept, and applying theory to female cyber victimization. During the empowerment process, the victim could be able to exert more control than the perpetrators, or victims may be able to develop the ability to change their situations. As a result of employing the empowerment theory, the negative consequences of cyber victimization can be mitigated.